The Collected Works of Samuel Taylor Coleridge, Volume 4 (Part II) : The Friend - Coleridge, Samuel Taylor; Rooke, Barbara E. (Princeton, NJ : Princeton University Press, 2015)
Published originally in 1809-1810, The Friend was revised in 1812, by public demand. In 1818, a three-volume rifacimento appeared in which Coleridge attempted to dispel obscurity, tie up loose threads of reasoning, and provide more mature apercus. Now, in the Collected Works, The Friend has been re-edited to return to Coleridge's 1818 text. His emendations, cuts, and marginal comments noted in six copies of the work, as well as manuscript additions and deletions, have been included as footnotes. The editor's footnotes also elucidate sources and themes and provide translations of the many Latin and Greek passages. The entire periodical Friend is given as an appendix, with the 1812 revisions.Originally published in 1969.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- List of Illustrations -- APPENDIX A. THE FRIEND (1809-10, 1812) -- No. 1. June 1, 1809 -- Prospectus -- No. 2. June 8, 1809 -- No. 3. August 10, 1809 -- No. 4. September 7, 1809 -- No. 5. September 14, 1809 -- No. 6. September 21, 1809 -- No. 7. September 28, 1809 -- No. 8. October 5, 1809 -- No. 9. October 12, 1809 -- No. 10. October 19, 1809 -- No. 11. October 26, 1809 -- No. 12. November 9, 1809 -- No. 13. November 16, 1809 -- No. 14. November 23, 1809 -- No. 15. November 30, 1809 -- No. 16. December 7, 1809 -- No. 17. December 14, 1809 -- No. 18. December 21, 1809 -- No. 19. December 28, 1809 -- No. 20. January 4, 1810 -- January 11, 1810 -- No. 21. January 25, 1810 -- No. 22. January 31, 1810 -- No. 23. February 8, 1810 -- No. 24. February 15, 1809 [1810] -- No. 25. February 22, 1810 -- No. 26. March 1, 1810 -- No. 27. March 15, 1810 -- Appendix B. Colophons of The Friend -- Appendix C. 1. The Manuscript of The Friend; 2. Annotated Copies -- Appendix D. Collation Tables -- Appendix E. Subscribers to the Periodical Friend -- Appendix F. Letters Concerning The Friend -- Appendix G. The Fable of the Madning Rain -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: English literature -- 19th century; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh